The experience of a nationwide Community of Practice to set up Regional Prevention Plans in Italy - Angela Giusti; Alberto Perra; Flavia Lombardo (BMC, 2017)
Abstract Background In 2010, the Italian Ministry of Health decided to start the planning process to elaborate the National Plan of Prevention 2010-2012 jointly with the 21 Regions. The National Institute of Health was responsible for supporting regional planners (RPs) by an original participatory approach of a web-based Community of Practice (CoP) to set up their own Regional Plans of Prevention. In this paper, we summarise the theoretical framework adopted, the main phases characterising the lifecycle of the nationwide CoP, the evaluation approach adopted and its findings. Methods Following the CoP theoretical framework from Wenger, an initial group of RPs were trained on Project Cycle Management as a planning method and thereafter they started interacting on a web-based Moodle platform for 8 months. The CoP evaluation mainly took into account aspects of 'immediate value', such as members interactions within the website, and several quantitative and qualitative tools were used to monitor changes over time. Data were retrieved from Moodle statistics or directly from the RPs by the means of a Knowledge, Attitude and Practice survey, a reaction survey, SWOT analysis and focus groups. Results The level of individual RPs knowledge increased after the initial course from 55.7% to 75%, attitudes and competence perception about the planning process method also showed an overall favourable change. During the CoP life span, the number of members increased from the original 98 RPs to include up to 600 new members on the basis of spontaneous demand. From April 2010 to January 2011, the 'vital signs' of the CoP were monitored, including RP logins (13,450 total logins and 3744 unique logins), views (27,522) and posts (1606) distributed in 326 forum discussion threads. Data and information retrieved from quantitative and qualitative evaluation approaches proved to be useful for the management and follow-up of the CoP. Conclusions The CoP experience was successful as 19 out of 20 Regions submitted their Regional Preventive Plan to their Ministry of Health within the due deadline. The CoP has proved to be an approach able to optimise resources and expertise, capitalising and generating new knowledge. However, more efforts should be deployed to define innovative ways to evaluate its values, tangible and intangible, as well as the return of investment.